1997
DOI: 10.1111/j.1600-0773.1997.tb01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Enrofloxacin after Oral Administration to Fed and Fasted Pigs

Abstract: The disposition of enrofloxacin was measured after intravenous and oral administration to pigs. Eight clinically healthy pigs weighing 25 to 40 kg received a dose of 5 mg/kg intravenously and 10 mg/kg orally in both a fasted and a fed condition in a three-way cross-over design. Enrofloxacin was present in plasma for up to 72 hr after both intravenous and oral administration to fasted as well as fed pigs. The steady state volume of distribution was determined to 3.950.5 Vkg body weight which indicates that enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…However, as documented by Garcia Ovando et al (1999) the conversion of enrofloxacin to ciprofloxacin is slow. They and others showed that only 10% of enrofloxacin was converted to ciprofloxacin in chickens and other species (Intorre et al 1997;Nielsen and Gyrdhansen 1997;Garcia Ovando et al 1999). It is unclear whether any such conversion occurs in vitro in tendon cells.…”
Section: Discussionmentioning
confidence: 95%
“…However, as documented by Garcia Ovando et al (1999) the conversion of enrofloxacin to ciprofloxacin is slow. They and others showed that only 10% of enrofloxacin was converted to ciprofloxacin in chickens and other species (Intorre et al 1997;Nielsen and Gyrdhansen 1997;Garcia Ovando et al 1999). It is unclear whether any such conversion occurs in vitro in tendon cells.…”
Section: Discussionmentioning
confidence: 95%
“…Enrofloxacin and ciprofloxacin from the plasma were subjected to liquid-liquid extraction according to the method of Nielsen and Hansen [7]. To 0.5 mL of plasma, 0.75 mL of acetonitrile was added in the ratio of 1:1.5.…”
Section: Drug Assaymentioning
confidence: 99%
“…(); found ciprofloxacin at concentrations below the LLOQ (0.13 μg/ml) after oral enrofloxacin administration. Low conversion of enrofloxacin to ciprofloxacin has been reported in chickens (Knoll, Glunder, & Kietzmann, ), foals (Bermingham, Papich, & Vivrette, ), and pigs (Nielsen & Gyrd‐Hansen, ) and may be due to reduced biotransformation of enrofloxacin to ciprofloxacin or rapid elimination of ciprofloxacin. Although fluoroquinolones are categorized as CYP1A2 inhibitors in people and dogs (Fish, ; Regmi, Abd El‐Aty, Kuroha, Nakamura, & Shimoda, ), the biotransformation pathway that converts enrofloxacin to ciprofloxacin in other species has not been reported. Enrofloxacin and marbofloxacin binding to plasma proteins: Medicines circulate with a proportion bound to plasma proteins, with the unbound proportion therapeutically active (Lindup & Orme, ).…”
Section: Anti‐infectivesmentioning
confidence: 99%